The Use of Heroic History R.A. Kartini as Reading Material in Assessing the Student Reading Comprehension - Elli Setiyo Wahyuni (Magister Scientiae, 2014)
The improvement of student reading skill involves some efforts in choosing the authentic material. The use of a heroic story, R.A. Kartini gives moral impacts for students’ character building and language skills improvement. The reading assessment provides some activities which explores the content of the reading text. The activities are identifying the good reader behaviors that have been taught and assessed, collecting evidence that is related to the good reader behaviors, analyzing the evidence on the good reader behaviors, and making an instructional decision to improve the reading skill. The advantages of using reading assessment activities to assessed the student reading comprehension are students participate in giving opinion, able to attach meaning to words or sentences, make summary prediction, describe the problem, give relevant solutions, retell the story in chronological order, and use prior knowledge in implementing the moral value. The analysis shows that students have the good reader behaviors as it is proven from their checklist score. The reading assessment gives result that portfolio is a recommended activity to improve the student reading comprehension.